The existential threat from cyber-enabled information warfare. (4th July 2019) - Lin, Herbert
ABSTRACT: Corruption of the information ecosystem is not just a multiplier of two long-acknowledged existential threats to the future of humanity – climate change and nuclear weapons. Cyber-enabled information warfare has also become an existential threat in its own right, its increased use posing the possibility of a global information dystopia, in which the pillars of modern democratic self-government – logic, truth, and reality – are shattered, and anti-Enlightenment values undermine civilization as we know it around the world.